Becoming redundant: Australian women's experiences of pregnancy after being unexpectedly scheduled for a medically necessary term elective cesarean section - Bayes, S.; Fenwick, J.; Hauck, Yvonne (Springer Publishing Company, 2012)
PURPOSE: There is now a comprehensive body of evidence reporting the effects of emergency cesarean section on women's emotional well-being. How women respond to becoming in need of a medically necessary elective cesarean section, however, has not previously been reported. This article describes and explains how a cohort of Australian women experienced the remainder of the antenatal period following the discovery during pregnancy of a medical reason to book a term elective cesarean section. DESIGN: Grounded theory methodology was used for this study. FINDINGS: Seven categories emerged from data analysis to represent the women's responses to becoming in need of a medically necessary term elective cesarean section. Four categories describe women's actions and interactions as they dealt with their lost expectations and their perceived “displacement” from their baby's birth. The other three categories represent the factors that mediated, or caused, women's responses. MAIN CONCLUSIONS: This study provides new knowledge about how women experience and respond to an unwanted and unforeseen change in their childbearing journey. The sense of disappointment and loss that is likely to arise for women who must “change track” must be anticipated, recognized, acknowledged, and when possible, forestalled by maternity care professionals.